(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
The study aimed to investigate the extent to which high school chemistry, earth science, and environmental sciences textbooks incorporate nano-technology and green chemistry applications. To achieve this, a descriptive analytical approach was used, and a content analysis checklist was developed, involving (68) indicators distributed across two domains: nanotechnology applications and green chemistry applications. The validity and reliability of the checklist were verified. The study sample included eight textbooks of chemistry plus earth and environmental sciences for the first and second high school grades. The results showed that the degree to which all textbooks addressed nanotechnology and green chemistry applications were moderate or below. In chemistry textbooks, the energy domain within nanotechnology applications and the environment and pollution prevention domains within green chemistry applications ranked first, with a moderate level of inclusion. In earth and environmental science textbooks, the energy domain within nanotechnology applications ranked first but with a low level of inclusion, while the environment and pollution prevention domains within green chemistry applications ranked first with a moderate level of inclusion. The results also revealed statistically significant differences in the extent to which chemistry plus earth and environmental science textbooks incorporated nanotechnology applications, in the favor of the earth and environmental science textbooks. Similarly, statistically significant differences were found in the inclusion of green chemistry applications, to the advantage of the chemistry textbooks.